Punk Faith: How Muslim Punks Use Their Voices for Social Change and Community Engagement - Solahudin, Dindin; Rojudin, Rojudin (Jurnal Iman dan Spiritualitas, 2025)
The interplay between religion and subculture presents a fascinating lens to examine social change, particularly in urban contexts. This study explores the phenomenon of Muslim Punk communities in Indonesia, a unique fusion of global subcultural identities and local Islamic values. Grounded in the discourse of globalization and transnationalism, the research highlights how subcultures transcend national boundaries, adapting to local norms and religious contexts while maintaining their core identity. Utilizing a phenomenological approach, data were collected from 24 community members (21 males and 3 females) aged 18–30 years, through in-depth interviews, observations, and field notes. The findings reveal that permissive parenting and rebellion against authoritarian familial structures are significant factors driving individuals toward the punk subculture. However, the research also uncovers a significant correlation between religious intensity and community detachment, with heightened religious adherence prompting individuals to reconsider behaviors conflicting with Islamic principles. Quantitative analysis of religious practices, such as daily prayers, fasting, and Quran recitation, coupled with qualitative insights into community dynamics—such as dress codes, substance use, and social rituals—illustrates how religiosity influences self-regulation and social conformity. The study concludes that increased religiosity reduces deviant behaviors, fostering a shift away from subcultural attachment. This phenomenon underscores the innate human inclination toward spiritual fulfillment, transcending subcultural identities and societal norms. By examining the intersection of religion and subculture, this research contributes to broader discussions on globalization, social change, and identity formation in developing countries. It provides critical insights into how global subcultures adapt to localized religious and moral frameworks, offering a valuable perspective for understanding the dynamic interplay between culture and spirituality in an increasingly interconnected world.